ENHANCING UTAUT FRAMEWORK TO EXPLAIN ACTUAL USAGE OF THE SINAU DIGITAL LEARNING MANAGEMENT SYSTEM WITH BEHAVIORAL INTENTION AS MEDIATING VARIABLE - Nadhifah; Farij Ibadil Maula (Universitas Negeri Surabaya, 2025)
Phenomenon/Issue: The massive digital transformation in academia has integrated technology into teaching and learning. As an adaptive learning tool, LMS can optimize the management of academic information and learning activities. The students, in the faculty of economics and business, used LMS with various backgrounds and different levels of experience Purpose: This study aims to examine usage behavior on the Sinau Digital Learning Management System educational platform through the application of the UTAUT model. Novelty: This study was conducted in the context of technology acceptance in the academic field by developing UTAUT theory through role of Behavioral Intention. Research Methods: This study used quantitative approach based on a survey of 344 students. The data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). Results:All hypotheses in this study were accepted. Each variable in the UTAUT model has a significant effect either directly or through the mediating variable of behavioral intention. Research Contributions: The study expands the UTAUT framework by integrating Behavioral Intention as a mediator in LMS use, offering insights for optimizing system development in higher education.